Supporting Factors of the Implementation that Impacting on the High Visits of Lawang Sewu Museum in Semarang - Prayoga, Arf; Hanani, Retna (Journal of Public Policy and Management Review, 2021)
Lawang Sewu Museum is one of the famous tourist sites in Semarang. Based on the high interest of tourists visiting Lawang Sewu Museum, it is a good achievement for the manager in managing and developing this tourist attraction. It's an achievement because, in fact, people's interest in a museum in today's modern era is relatively low. From 2015 to 2019, the number of tourists from Lawang Sewu Museum has always increased. It even increased in up to thousands of tourists each month. The purpose of this study is to see what is the factors that affecting the implementation of the development and management of Lawang Sewu Museum. This study used a qualitative descriptive approach. Data collection techniques include: observation, interviews, and documentation. The results of this study indicate that the manager of Lawang Sewu Museum is successful in developing and managing it, so it is desirable by the tourists. But there are still some evaluations that need to be done, such as staff recruitment and lack of funds in building expensive maintenance. Factors that affect the development and management of Lawang Sewu Museum are communication, resources, disposition, and bureaucratic structure. In this study, researchers suggest conducting employee recruitment and a continuous collaboration between the management and the Local Government.